ROLE OF PRIVATE SECTOR IN PROMOTING IPM PRACTICES AMONG FARMING COMMUNITY IN PUNJAB, PAKISTAN - S. Ali; M. Ahmad; T. Ali; B. Shahbaz; G. A. Khan; M. Iftikhar; F. Nosheen (Journal of Animal and Plant Sciences, 2013)
Due to an aggressive use of pesticides on crops, the insect pests have developed resistance, posing a serious threat to the agriculture in Pakistan. This situation highlights the need to promote IPM among farming community. Private sector in Pakistan has been actively engaged in agricultural extension services since 1988. Currently, about 500 pesticide companies are working in private sector and providing plant protection advisory services to the farmers. This study investigated the role of private sector in promoting IPM practices among the farming community in Punjab, Pakistan. Sixty (60) extension personnel of a private extension agency and some 408 farmers were selected for interview by using simple random sampling technique through Fitzgibbon table. The data were collected through validated interview schedule and analyzed by using SPSS. The results of the study revealed that the mean value for the physical, cultural, and biological control methods, was below 2 indicating that pesticide companies are less interested to promote IPM practices. Farmers also reported that private extension staff emphasized on the aggressive use of pesticides rather its judicious use. It is suggested that private sector should not recommend an extensive use of pesticides and make efforts to promote other pest control methods in combination with chemical control.
Keywords: private sector; IPM; farming community